PENGARUH KUALITAS LAYANAN, REPUTASI, DAN NILAI LAYANAN PERGURUAN TINNGI TERHADAP KEPUASAAN MAHASISWA - A. J. Ibnu Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Currently, there is a tight competition in service industry, especially in higher education or university. The administrators or universities have to understand deeply their students and try to fulfill their needs well to make them satisfied and tell positive word-of-mouth about the university. Therefore, the understanding of student satisfaction and other factors determining student satisfaction, such as service quality, reputation, and service value of the university, become very important. The objectives of this study are to know whether there are positive effects of service quality and reputation on service value. Furthermore, this study also try to verify whether there are positive effects of service quality and value on student satisfaction. Results indicate that most of the empirical data support that there are positive effects of service quality and reputation on service value. Likewise, this study proves that there is a positive effect of service value on student satisfaction. However, this study also find that there is not a positive effect of service quality on student satisfaction.